Design of Temperature Control in Air Conditioner Using Self-Tuning PID Based on Fuzzy-Mamdani - Silitonga, Daniel; Wahyudi, Wahyudi (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2025)
Air Conditioner (AC) is a form of technological advancement in air conditioning. The consumption of AC in society is also very high at 48% using AC for 8-12 hours per day. This data is according to the Indonesian Consumers Foundation (YLKI). There are many factors behind this very long use. In this article try to see the AC factor that has not efficiently obtained the temperature setpoint value causing excessive use. When the AC gets the setpoint from the remote control. The actuator component in the form of a Peltier will work to achieve that value. This design will be carried out in order to create a PID control that performs tuning with the Fuzzy-Mamdani method in order to obtain the appropriate PID coefficient value. The test results from the Self-Tuning PID controller have a faster steady state time in all tests. In each test of the fixed reference value. The test of the changing reference value. and the test with the disturbance signal in the form of a step Self-Tuning PID have a faster time of 6.273 s. 3.364s and 5.4545s respectively. For the performance evaluation index, the Self-Tuning PID controller tends to have smaller ISE, IAE, and ITAE values in each test compared to the existing PID controller.